Peran Guru PJOK dalam Mengatasi Siswa Sekolah Dasar Kelas Tinggi yang Hiperaktif - Hilmiyah Khumairotuz Zuhroh; Sunanto Sunanto; Muhammad Thamrin Hidayat; Afib Rulyansah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study was conducted to analyze the role and method of PJOK teachers to overcome the hyperactive students of SD Tunas Bhakti 26 during the V grade PJOK learning. It is done in an individual, unified and comprehensive way. Data collection techniques through observation, interviews and documentation. Studies have shown that hyperactive students tend to lose focus and remain silent for long periods of time. Teachers need a special approach to keep them interested in learning activities. During the learning activity, there were obstacles in the research process. That is, (1) the students got bored easily and found it difficult to sit quietly on their respective benches. (2) Hyperactive students easily ignore teacher warnings. (3) The hyperactive student has difficulty working in groups, such as when discussing with classmates. Based on the results of existing research, it can be concluded that hyperactive students tend to be unable to focus and remain silent for a long time. Teachers need a special approach to interest them in learning activities.